2003
DOI: 10.1084/jem.20022112
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Fyn Through Translocation of Activated Lck into Lipid Rafts

Abstract: Whether or how the activation of Lck and Fyn during T cell receptor (TCR) signaling is coordinated, and their delivery of function integrated, is unknown. Here we show that lipid rafts function to segregate Lck and Fyn in T cells before activation. Coaggregation of TCR and CD4 leads to Lck activation within seconds outside lipid rafts, followed by its translocation into lipid rafts and the activation of colocalized Fyn. Genetic evidence demonstrates that Fyn activation is strictly dependent on receptor-induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
116
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(136 citation statements)
references
References 25 publications
19
116
1
Order By: Relevance
“…They may function redundantly and independently. However, Julius and co-workers recently proposed a mechanistic link for activation of each kinase, involving differences in their lipid raft localization (Filipp et al, 2003). After crosslinking primary T cells with anti-TCR and anti-CD4 antibodies, they observed a kinetic discrepancy in kinase activation, with Lck activity peaking early and Fyn lagging behind, all within the first 2 min after stimulation.…”
Section: Model Of Regulation and Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…They may function redundantly and independently. However, Julius and co-workers recently proposed a mechanistic link for activation of each kinase, involving differences in their lipid raft localization (Filipp et al, 2003). After crosslinking primary T cells with anti-TCR and anti-CD4 antibodies, they observed a kinetic discrepancy in kinase activation, with Lck activity peaking early and Fyn lagging behind, all within the first 2 min after stimulation.…”
Section: Model Of Regulation and Activationmentioning
confidence: 99%
“…Fyn activation (both in and out of rafts) markedly increased after initial Lck activity and even increased after Lck activity had waned. Importantly, Filipp et al (2003) showed that Fyn could not be activated in Lck-deficient T cells. This study suggests a model whereby Lck: (1) is initially activated outside of rafts; (2) then translocates into rafts; and (3) then activates Fyn molecules already residing in rafts.…”
Section: Model Of Regulation and Activationmentioning
confidence: 99%
“…c-Cbl itself is activated by tyrosine phosphorylation on several residues, most importantly Y700, Y731 and Y774 [13,[15][16][17]. These residues are not, however, substrates of Lck or but of Fyn and Syk [13,16,18,19], which are activated directly or indirectly by Lck [20].…”
Section: Introductionmentioning
confidence: 99%
“…c-Cbl itself is activated by tyrosine phosphorylation on several residues, most importantly Y700, Y731 and Y774 [13,[15][16][17]. These residues are not, however, substrates of Lck or but of Fyn and Syk [13,16,18,19], which are activated directly or indirectly by Lck [20].Cbl exists in two main isoforms, c-Cbl and Cbl-b, with a high level of sequence conservation. Consistent with the negative regulation assigned to the Cbl family of proteins, T cells from c-Cbl À/À and Cbl-b À/À mice were hyperactive upon TCR engagement, although some biochemical distinctions between the phenotypes exist [21][22][23][24][25].…”
mentioning
confidence: 99%
“…Analysis of mice deficient in Lck, Fyn, or both SFKs has determined that Lck is the predominant SFK required to initiate TCR signaling in thymocytes and mature T cells. However, current models of TCR activation put Fyn downstream of Lck activation, with Lck translocating to lipid rafts upon TCR stimulation to activate raft-associated Fyn (35,36) by an as yet undetermined mechanism. An intriguing possibility is that PTP␣ is a target of Lck, thus promoting PTP␣ function as a Lck effector and a Lck/Fyn signaling intermediate.…”
Section: Discussionmentioning
confidence: 99%